Presenting approaches to stress management in the elderly in Qazvin - Saeidabadi, Hamzeh; Yari, Saeed; Jaddi Madarsara, Tayyebeh; Ahmadian Kudakan, Navid (Asian Pacific Journal of Environment and Cancer, 2019)
Background: Based on the opinions of the World Health Organization (WHO), the elderly period begins at the age of 60 in third world countries. During this period the amount of social activities are reduced and as a result of which, the person is far more exposed to solitude and physical problems (i.e. high blood pressure, diabetes, etc.) and mental illnesses (i.e. depression etc.). Therefore, considering the continuous growth in the population of the elderly in Iran, management of stress is crucial in order to lengthen their quality life-time, and reduce direct and indirect compensations to the government and also to families. Methods: This survey was conducted in a descriptive- analytical method in Qazvin in 2019, and the questionnaires were filled by eligible participants after reforming the questionnaire twice based on 0.71 (Cronbach’s alpha) confirmation. In order to prove the validity and reliability of the data, mentioning any personal information were strictly avoided, and later 30 participants were taken part in the research. Results: Considering the fact that in order to manage the stress, the participants’ mental conditions need to be mainly addressed, which are indeed source of numerous diseases, conducting daily activities, trusting families and societies is very effective in their self-acceptance. Addressing personal requirements including: 1. Individual quality life-time. 2. Medical facilities and services, 3. Public transportation services, and self-care, are potentially the most important issues to the elderly. Conclusion: Based on the conducted survey, many activities have been done to help the elderly manage their stress. However, considering the increasing population of the elderly, there are many more activities yet to be done operationally and tangibly. Although holding training sessions might be promising and motivating, but as a result of countless social difficulties, caused by lack of facilities, and lack of positive or supportive view by the community, the role of such phenomenon will most probably be passive and fleeting. Doing physical exercise can be an effective and cheerful element, and also preventive to the occurrence of many physical and mental illnesses. It should also be noted that many of the current problems are actually caused by urban factors (e.g. sidewalks, sport centers, etc.) which need to be immediately addressed by the government. Keywords: Stress management, Life satisfaction, Elderly